The Heritage of Freges Begriffsschrift - Švob, Goran (Array, 2000)
We discuss three Fregean topics and trace their source to Begriffsschrift. First, Freges theses of declarative sentences as names of truth values, strange as it might appear to his readers, came rather naturally to Frege after his treatment of truth-functional equivalence as identity in Begriffsschrift. Second, the use of assertion sign in Freges later work undoubtedly originates in Begriffsschrift, but Freges later account of its role differs very much from that in Begriffsschrift. Finally, we consider the suggestion in Begriffsschrift, that identity pertains to signs and not to objects. It was later abandoned by Frege and neglected by the mainstream of philosophical tradition, though it was one of the rare constant philosophical convictions of Wittgenstein.